THE QUALITY INDEXES ESTIMATION METHOD OF THE PHASE-LOCKED LOOP SYSTEM - Yevhen V. Lebid; Serhii M. Kononenko; Yevhen O. Sudnikov; Ruslana H. Yefimova (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The of article includes the definition of the dynamic, meansquared errors and quality of transients of the phase - locked loop (PLL) caused by the changes of the master and disturbing impacts, its differential coupling was synthesized under conditions of increasing the dynamic accuracy and fast response in the complex roots of the characteristic equation. The paper provides a comparative evaluation of the PLL dynamic characteristics.